THE EFFECT OF A MAGNETIC WAVE ON THE CARDIOVASCULAR SYSTEM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article discusses how magnetic waves affect the heart and vascular system. Scientific research related to electromagnetic waves is developing day by day and yields interesting results regarding their effect in medicine, especially on the heart and vascular system. This article aims to examine the effect of magnetic waves on the functioning of the cardiovascular system, determining its negative or positive aspects.